Unraveling the Employability Paradox: The Impact of Compensation and Training on Turnover Intention in the Airline Catering Industry - Rina Syafitri; Nidya Dudija (Sharia Economic and Management Business Journal (SEMBJ), 2026)
Background: Retaining skilled employees in the high-pressure airline catering sector remains a critical organizational challenge, particularly in labor-intensive environments characterized by operational demands, strict service standards, and limited career mobility. Compensation and training are commonly recognized as strategic human resource practices to reduce turnover intention and strengthen employee attachment. However, empirical findings remain inconsistent, especially regarding the mediating role of employee engagement in explaining employee retention behavior across hierarchical organizational levels.Method: This study employed a quantitative cross-sectional research design. Primary data were collected through systematic random sampling involving 175 permanent employees from various hierarchical levels at an Indonesian airline catering company. Data were analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) to examine the direct and indirect relationships among compensation, training, employee engagement, and turnover intention.Results: The findings demonstrate that fair compensation significantly reduces turnover intention while simultaneously enhancing employee engagement across organizational departments. In contrast, training programs positively influence employee engagement but fail to significantly suppress turnover intention. The results further reveal an employability paradox, where extensive training investments increase employees’ external marketability when not accompanied by clear internal career advancement opportunities. Moreover, employee engagement does not mediate the relationship between training and turnover intention, indicating the collapse of engagement as a psychological retention mechanism within the organizational context studied.Conclusion: The study concludes that for mature employees operating across multiple organizational layers, retention is driven more strongly by direct economic exchange mechanisms than by affective emotional attachment. Compensation remains the most effective retention instrument, whereas training initiatives without structured career pathways may unintentionally encourage employee mobility toward external opportunities. These findings highlight the importance of aligning organizational development programs with long-term internal career strategies to strengthen workforce retention in the airline catering industry.